Interpreting de novo Variation in Human Disease Using denovolyzeR. (6th October 2015) - Ware, James S.; Samocha, Kaitlin E.; Homsy, Jason; Daly, Mark J.
Abstract: Spontaneously arising ( de novo ) genetic variants are important in human disease, yet every individual carries many such variants, with a median of 1 de novo variant affecting the protein‐coding portion of the genome. A recently described mutational model provides a powerful framework for the robust statistical evaluation of such coding variants, enabling the interpretation of de novo variation in human disease. Here we describe a new open‐source software package, denovolyzeR, that implements this model and provides tools for the analysis of de novo coding sequence variants. © 2015 by John Wiley & Sons, Inc.